The effect of interviewer personality, skills and attitudes on respondent co-operation with face-to-face surveys - Annette Jäckle; Peter Lynn; Jennifer Sinibaldi; Sarah Tipping (University of Essex, Institute for Social and Economic Research (ISER), 2011)
This paper examines the role of interviewers' experience, attitudes, personality traits and inter-personal skills in determining survey co-operation. We take the perspective that these characteristics influence interviewers' behaviour and hence influence the doorstep interaction between interviewer and sample member. We use a large sample of 842 face-to-face interviewers working for a major survey institute and analyse co-operation outcomes for over 100,000 cases contacted by those interviewers over a 13-month period.
Keywords: C83; 330; non-response; interviewer survey; Big Five personality traits; Meinungsforschung; Befragung; Persönlichkeitspsychologie; Kooperation